2017
DOI: 10.1007/s10792-017-0503-9
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of choroidal osteoma complicating choroidal neovascularization by optical coherence tomography angiography

Abstract: PurposeChoroidal osteoma (CO) frequently leads to progressive visual loss due to complications of secondary choroidal neovascularization (CNV).We report herein the function of optical coherence tomography angiography (OCTA) in observation of CO complicating CNV.MethodsA 25-year-old female presented to our hospital with chief complaint of sudden unilateral visual acuity decrease for one week, with metamorphopsia in the left eye. Her best corrected visual acuity was 0.12 in the left eye. Then complete ophthalmol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 15 publications
(19 reference statements)
1
8
0
Order By: Relevance
“…Therefore, within this population, CNV has a relatively high occurrence and is a significant cause for visual morbidity and may portend a poor long-term visual prognosis [ 2 ]. Many reported cases of CNV and associated subretinal fluid in CO have resolved with a series of up to four anti-VEGF injections [ 4 , 5 , 6 , 7 ]. Our case required ten monthly injections of ranibizumab suggesting a more aggressive or refractory secondary CNV than those previously reported.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, within this population, CNV has a relatively high occurrence and is a significant cause for visual morbidity and may portend a poor long-term visual prognosis [ 2 ]. Many reported cases of CNV and associated subretinal fluid in CO have resolved with a series of up to four anti-VEGF injections [ 4 , 5 , 6 , 7 ]. Our case required ten monthly injections of ranibizumab suggesting a more aggressive or refractory secondary CNV than those previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…CNV was seen most commonly in tumors with an irregular surface or overlying hemorrhage. Optical coherence tomography angiography (OCT-A) has been shown to be effective in evaluating CNV in patients with CO and those treated with anti-vascular endothelial growth factor (anti-VEGF) therapy [ 3 , 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Optical coherence tomography angiography (OCTA) is a noninvasive imaging modality for depth-resolved visualization of retinal vasculature, which provides a high-resolution image of the microvasculature of the different layers in the retina. [ 3 ] It can detect the CNV and observe the morphology and flow areas of CNV without obscured details due to dye leakage in CO. [ 4 ]…”
Section: Introductionmentioning
confidence: 99%
“…5 Several case reports have shown that OCTA is useful in detecting CNV secondary to choroidal osteoma. [6][7][8][9][10] However, choriocapillaris characteristics in choroidal osteoma have not been a focus in OCTA imaging. This study aims to evaluate the morphological findings of the choriocapillaris via OCTA in choroidal osteoma.…”
Section: Introductionmentioning
confidence: 99%